MODERN APPROACHES TO THE FORMATIZATION OF RETAILERS - DRAZHNYTSIA, Sergii; LYKHOHOD, Oleksander; YARMOLYUK, Yaroslav (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In this article, the authors specify the main classification features of retail trade enterprises at the current stage of their development, and also provide the main characteristics, principles and approaches to the definition (formation) of modern formats of retailers (formatting). Thus, it was determined that there are five main types of retailers, within which a number of different formats operate. The definition of the format of a retailer almost corresponds to the definition of its format, but is broader and characterizes in more detail the main indicators of a retail trade enterprise, such as forms and methods of trade service, price and assortment policies of the enterprise, its size and status, affiliation, etc.The authors also analyzed and compared formatting parameters of retailers in European and American countries in the article. It was determined that the main parameters that determine the format of a retailer in America are characterized by much higher indicators than in European countries.Based on the analysis, the authors identified a number of common features and deviations in the process of formatting retailers in Europe and America and their classification, as well as proposed specific criteria and approaches to the formatting of retailers in Ukraine at the current stage. Taking into account the European integration vector of the development of the national economy of Ukraine and in order to ensure a quick and high-quality transition of Ukraine to the European standards of trade service and unification, the authors recommend implementing the European model into the domestic practice of formatting retail trade enterprises.
Keywords: format of trading company; type of trading company; formatting of retailers; typification of trading companies; types of trading companies